The endoscopic prediction model of simple endoscopic score for Crohn’s disease (SES-CD) as an effective predictor of intestinal obstruction in Crohn’s disease: A multicenter long-term follow-up study - Xu, Weimin; Hua, Zhebin; Wang, Yaosheng; Gu, Yubei; Zhong, Jie; Cui, Long; Du, Peng (Frontiers in Surgery, 2022)
Background: The simple endoscopic score for Crohn's Disease (SES-CD) is a widely used index to evaluate clinical and endoscopic activity. However, the association and predictive value of SES-CD for intestinal obstruction in Crohn's Disease (CD) remains unclear. We aimed to establish the best cut-off indicators of SES-CD for early clinical intervention and subsequent prevention of intestinal obstruction in CD. Methods: Data on patients with CD evaluated at our institute from January 2016 to January 2022 were retrospectively collected. The SES-CD and Crohn’s Disease Activity Index (CDAI) scores used in the analysis indicated the results of the first clinical and colonoscopy evaluations after hospitalization. The primary outcome was the occurrence of intestinal obstruction during admission and follow-up. Results: A total of 248 patients with a median follow-up time of 2.0 years (interquartile range [IQR]: 1.0 - 4.0) were enrolled, of which 28.2% developed intestinal obstruction. An SES-CD score of 8 was the most significant threshold evaluation, and SES-CD ≥ 8 had the largest area under the receiver-operating characteristic curve (0.705), with a sensitivity of 52.9% and specificity of 88.2% in predicting intestinal obstruction. Furthermore, SES-CD ≥ 8 had the greatest risk factor for intestinal obstruction (odds ratio: 7.731; 95% confidence interval: 3.901 -15.322; p < 0.001) and significantly decreased the overall intestinal obstruction-free survival (p < 0.001). Conclusion: The SES-CD endoscopic prediction model could be an effective predictor of intestinal obstruction in patients with CD. More frequent follow-up and colonoscopic surveillance should be considered in patients with SES-CD score ≥ 8 to prevent the development of intestinal obstruction.